Conventional Laparoscopy Is the Better Option for Tubal Sterilization Reversal: A Closer Look at Tubal Reanastomosis - Anita Madison; Lamia Alamri; Adina Schwartz; Marja Brolinson; Alan DeCherney (Women's Health Reports, 2021)
Background: Permanent sterilization is one of the most common methods of birth control in the United States and around the world. A small subset of women will regret their decision and desire future fertility. For these women, the options include in vitro fertilization (IVF) or surgical reversal. Surgical reversal, specifically via tubal reanastamosis, is an important choice to consider. Surgical reversal can be accomplished via three different general approaches including laparotomy, conventional laparoscopy, and robot-assisted approaches. Unfortunately, surgical reversal is becoming a lost art. Objective: To compare and contrast pregnancy success rates, ectopic pregnancy rates, and cost between the surgical methods and IVF. Methods: We conducted a literature review via Pubmed with keywords as listed below. Conclusion: Laparoscopic tubal reanastomosis is the best approach for women <40 years of age due to pregnancy outcomes that are comparable to other methods, cost effectiveness, and favorable safety profile of minimally invasive surgery.